2004
DOI: 10.1063/1.1853204
|View full text |Cite
|
Sign up to set email alerts
|

The supersymmetric method in random matrix theory and applications to QCD

Abstract: Abstract.The supersymmetric method is a powerful method for the nonperturbative evaluation of quenched averages in disordered systems. Among others, this method has been applied to the statistical theory of S-matrix fluctuations, the theory of universal conductance fluctuations and the microscopic spectral density of the QCD Dirac operator.We start this series of lectures with a general review of Random Matrix Theory and the statistical theory of spectra. An elementary introduction of the supersymmetric method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 110 publications
2
38
0
Order By: Relevance
“…The width of fluctuations of hermitian degrees of freedom decreases with the system size as 1/ √ N and the aspect ratio τ of the elliptic ensemble (19) approaches minus one as τ = −1 + 4 α 2 /N . The evolution of the shape with α can be found using for instance the supersymmetric method [16]. Having done that one can try to relate the parameter α to β in QCD 3 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The width of fluctuations of hermitian degrees of freedom decreases with the system size as 1/ √ N and the aspect ratio τ of the elliptic ensemble (19) approaches minus one as τ = −1 + 4 α 2 /N . The evolution of the shape with α can be found using for instance the supersymmetric method [16]. Having done that one can try to relate the parameter α to β in QCD 3 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Much of the RMT machinery -such as the saddle-point method, orthogonal polynomials, the Efetov's supersymmetric technique, or the diagrammatic expansion and the free random variables calculus (see for example [23,24,25,26,27,28,29,30,31,32,33,34,35,36] for reviews; these last two techniques are used in this paper) -has been developed in the Hermitian context, and tailored for real spectra. The necessity of dealing with complex spectra demands enhancements of these methods.…”
Section: Non-hermitian Random Matrix Modelsmentioning
confidence: 99%
“…, L, with the cyclic convention 0 = L, where the normalized traces (22) have been used. Results (27), (28) mean that the four blocks of the matrix…”
Section: The Dyson-schwinger's Equationsmentioning
confidence: 99%
“…In particular, it has been shown that the SO(2,1) symmetry of a hyperbolic spin chain is spontaneously broken also in one and two dimensions. In essence, the reason is that a partition function with a noncompact symmetry can only be defined if this symmetry is spontaneously broken to its compact subgroup SO (2). In a conformal invariant theory the spectral density of the Dirac operator also scales as ρ(λ) ∼ V λ α and this scenario might reconcile conformal behavior with universal random matrix statistics [15][16][17].…”
Section: Jhep07(2017)144mentioning
confidence: 99%
“…It has been well established that lattice QCD Dirac spectra fluctuate according to the corresponding random matrix theory in the microscopic domain (see [1][2][3]). Because this agreement is based on the spontaneous breaking of the flavor symmetry, one would expect that, as a consequence of the Coleman-Mermin-Wagner theorem, the agreement with Random Matrix Theory in two dimensions is structurally different from the agreement found in four dimensions.…”
Section: Jhep07(2017)144mentioning
confidence: 99%